IMGT® Biocuration and Comparative Study of the T Cell Receptor Beta Locus of Veterinary Species Based on Homo sapiens TRB - Pégorier, Perrine; Bertignac, Morgane; Chentli, Imène; Nguefack Ngoune, Viviane; Folch, Géraldine; Jabado-Michaloud, Joumana; Hadi-Saljoqi, Saida; Giudicelli, Véronique; Duroux, Patrice; Lefranc, Marie-Paule; Kossida, Sofia (Frontiers in Immunology, 2020)
IMGT®, the international ImMunoGeneTics information system® is the global reference in immunogenetics and immunoinformatics. By its creation in 1989 by Marie-Paule Lefranc (Université de Montpellier and CNRS), IMGT® marked the advent of immunoinformatics, which emerged at the interface between immunogenetics and bioinformatics. IMGT® is specialized in the immunoglobulins (IG) or antibodies, T cell receptors (TR), major histocompatibility (MH), and proteins of the IgSF and MhSF superfamilies. T cell receptors are divided into two groups, αβ and γδ TR, which express distinct TR containing either α and β, or γ and δ chains, respectively. The TRβ locus (TRB) was recently described and annotated by IMGT® biocurators for several veterinary species i.e. cat (Felis catus), dog (Canis lupus familiaris), ferret (Mustela putorius furo), pig (Sus scrofa), rabbit (Oryctolagus cuniculus), rhesus monkey (Macaca mulatta) and sheep (Ovis aries). The aim of the present study is to compare the genes of the TRB locus among these different veterinary species based on Homo sapiens. The results reveal that there are similarities but also differences including the number of genes by subgroup which may demonstrate duplications and/or deletions during evolution.